Assessment of Hearing Defect in Oral Submucous Fibrosis: A Cross-Sectional Study - Garikapati Anoop; Nunsavathu Purnachandra Rao Naik; Yalamanchili Samata; Saranu Sethu Manjusha; Chennupati Tejaswi (Journal of Orofacial Sciences)
Introduction: This study was designed to assess the hearing defect in oral submucous fibrosis and compare the hearing defect in different stages of oral submucous fibrosis (OSMF) and also the hearing defect in the control group. Assessment of hearing defect in OSMF. This present study consisted of a total of 120 subjects. Detailed history and thorough intraoral examination were done for the hallmark clinical features of OSMF. Materials and Methods: The staging was given depending on Inter incisal distance, given by Chandramani More et al. Patients were subjected to a pure tone audiometry. The same tests were performed even in the control group, and changes about different stages of OSMF were evaluated. A comparison was made between the study and the control group. Chi-square test, Lenovo test, and t-test were utilised for Statistical analysis. Results: Among 120 subjects, the total hearing loss was seen in 37 subjects. Among the total control group of 60 members, eight members showed hearing loss. Six OSMF patients of stage II showed hearing loss out of 23 and 16 OSMF patients of stage III showed hearing loss out of 19 and seven patients of OSMF stage IV, all of them showed hearing loss. Conclusion: In comparison of the OSMF study to the control group, there is an increased severity of hearing loss. Significant hearing loss is seen with different stages of OSMF. The severity of hearing loss is seen with an increase in the stage of OSMF. Both sensorineural and conductive hearing loss are seen with increasing stages of OSMF.